Development of a supplementary book based on research of the ground kangaroo (Dorcopsis luctuosa) for biology students in higher education - Febelina Febriana Sremere; Silvia Hanna Kusuma Sirait; Iwan Iwan (Journal of Research in Instructional, 2026)
This research aimed to develop a research-based supplementary book on ground kangaroos (Dorcopsis luctuosa) as teaching material for the Mammalogy course. The study used the Research and Development (R&D) method with the ADDIE model. The subjects were Biology Education students from the Faculty of Teacher Training and Education, University of Papua, who were taking the Mammalogy and New Guinea Biota Conservation course. The research instruments included an expert validation sheet, a student response questionnaire, and learning outcome tests (pre-test and post-test). The expert validation results showed an average percentage of 81.35%, categorized as highly valid. Student responses averaged 92.43%, categorized as highly practical. The supplementary book effectively improved students' learning outcomes from an average pre-test score of 64.55 to a post-test score of 95.58, with an N-Gain value of 0.88. Therefore, the supplementary book based on ground kangaroo (Dorcopsis luctuosa) research is suitable for use as supporting teaching material in the Mammalogy and New Guinea Biota Conservation course.